Age-related deficits in efficiency of low-level lateral inhibition - Schlaghecken, Friederike; Birak, Kulbir S.; Maylor, Elizabeth A. (Frontiers in Human Neuroscience, 2012)
In a masked prime task using a 0-ms prime-target inter-stimulus-interval, responses on compatible trials (prime and target match) are usually faster and more accurate than responses on incompatible trials (prime-target mismatch). This positive compatibility effect comprises benefits on compatible relative to neutral trials and costs on incompatible relative to neutral trials. Comparing performance in 2- vs. 4-alternative-response versions of the task indicates that benefits are due to direct priming of a motor response, whereas costs reflect inhibition of the alternative response tendency. The present study investigates whether normal aging is associated with a selective deficit in the inhibitory component, affecting both low-level motor and higher-level executive control. Testing 20 young and 20 older adults, we found that (a) overall, prime-induced benefits were of similar magnitude across age groups, but inhibition-based costs were smaller in older compared to young adults; (b) increasing the number of response alternatives caused the same pattern of unaltered benefits and reduced costs in both age groups; and (c) costs, but not benefits, in the 2-alternative condition were significantly predicted by scores on the digit-symbol substitution task (DSST), independently of age and other background variables. Results demonstrate the possibility of isolating an inhibitory component in low-level perceptuo-motor control. Importantly, this component shows an age-related decline in the absence of a corresponding decline of visuo-motor excitability, and appears to be linked to performance on a higher-level processing speed task. We hypothesize that aging might affect the brain's ability to establish precise short-term lateral inhibitory links, and that even in young adults, the efficiency of such links is a significant contributing factor in higher-level cognitive performance.